2022
DOI: 10.2196/36217
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Uptake of the COVID Coach App Among US Military Veterans: Funnel Analysis Using a Probability-Based Panel

Abstract: Background Although the COVID-19 pandemic has not led to a uniform increase of mental health concerns among older adults, there is evidence to suggest that some older veterans did experience an exacerbation of preexisting mental health conditions, and that mental health difficulties were associated with a lack of social support and increasing numbers of pandemic-related stressors. Mobile mental health apps are scalable, may be a helpful resource for managing stress during the pandemic and beyond, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…The finding that VA users were more likely to have used NCPTSD-developed apps is consistent with that of Hogan et al (2022), who similarly observed that being connected with VA care may help raise awareness of VHA health-related apps, including the mental health apps created by the NCPTSD. These findings also align with previous research among U.S. veterans focused the use of a single app within the portfolio (COVID Coach), where veterans with higher levels of education, greater smartphone utilization, two or more deployments, and a greater number of adverse childhood experiences were more likely to have tried the COVID Coach app (Jaworski et al, 2022).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The finding that VA users were more likely to have used NCPTSD-developed apps is consistent with that of Hogan et al (2022), who similarly observed that being connected with VA care may help raise awareness of VHA health-related apps, including the mental health apps created by the NCPTSD. These findings also align with previous research among U.S. veterans focused the use of a single app within the portfolio (COVID Coach), where veterans with higher levels of education, greater smartphone utilization, two or more deployments, and a greater number of adverse childhood experiences were more likely to have tried the COVID Coach app (Jaworski et al, 2022).…”
Section: Discussionsupporting
confidence: 88%
“…Accumulating evidence suggests that U.S. veterans are open to using apps to support health, and mental health apps developed by the VA and the Defense (DoD) have been found to be both feasible and acceptable (Gould et al, 2019;Hogan et al, 2022). With respect to the suite of apps developed by the VA's National Center for PTSD to address the self-management of mental health and wellbeing, there is a growing evidence base to suggest they can be of use for PTSD (Hallenbeck et al, 2022;Kuhn et al, 2014Kuhn et al, , 2017Miner et al, 2016;Owen et al, 2015;Possemato et al, 2016), COVIDrelated stress (Jaworski et al, 2021(Jaworski et al, , 2022, sleep problems (Koffel et al, 2018;Kuhn et al, 2022;Reilly et al, 2019), and the practice of mindfulness (Kozlov et al, 2020(Kozlov et al, , 2022. Although the evidence base to support these apps is growing, the research on these apps has been centered on two distinct types of studies-randomized controlled trials limited to participants who meet very specific study eligibility criteria, or "in the wild" evaluations of anonymous app analytics data, where no demographic, health, or any other identifying information about the app users is known.…”
Section: Creation and Adoption Of The Va's National Center For Posttr...mentioning
confidence: 99%
“…33 As of 2021, 85% of Americans reported owning a smartphone, 33 a number similar in magnitude to our sample (90%) and to other broader Veteran populations (81.5%). 34 Programs that support technology access may also support DHD adoption. For example, VHA’s Offices of Connected Care and Rural Health successfully supported tablet use by distributing tablets to Veterans experiencing barriers to in-person access, with the intention of supporting clinical video visits.…”
Section: Discussionmentioning
confidence: 99%